2021
DOI: 10.1007/s00586-020-06707-x
|View full text |Cite
|
Sign up to set email alerts
|

Spine surgeon perceptions of the challenges and benefits of telemedicine: an international study

Abstract: Introduction While telemedicine usage has increased due to the COVID-19 pandemic, there remains little consensus about how spine surgeons perceive virtual care. The purpose of this study was to explore international perspectives of spine providers on the challenges and benefits of telemedicine. Methods Responses from 485 members of AO Spine were analyzed, covering provider perceptions of the challenges and benefits of telemedicine. All questions were optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Neurosurgery, in particular, may have had a smoother transition to telemedicine due to the existing networks for teleneurology throughout the United States [17] . Another reason for the successful adoption of telemedicine in neurosurgery may be attributed to the finding that the majority of neurosurgeons were not concerned with the limitations imposed by telemedicine on conducting a physical examination virtually [18] . Urology may have had more telehealth encounters in view of higher baseline use prior to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgery, in particular, may have had a smoother transition to telemedicine due to the existing networks for teleneurology throughout the United States [17] . Another reason for the successful adoption of telemedicine in neurosurgery may be attributed to the finding that the majority of neurosurgeons were not concerned with the limitations imposed by telemedicine on conducting a physical examination virtually [18] . Urology may have had more telehealth encounters in view of higher baseline use prior to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As the use of telemedicine has increased massively during the COVID-19 pandemic, so has the research on the use of telemedicine ( Tandon et al, 2021 ; Shafi et al, 2021 ; Swiatek et al, 2021 ; Ryu et al, 2021 ; Zengin et al, 2021 ; Lovecchio et al, 2020 ; Mohanty et al, 2020 ; Riew et al, 2021 ) . Table 5 gives an overview of eight published survey results on the use of telemedicine during the COVID-19 pandemic among neurological and spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Another international study, involving 485 spine surgeons, assessed the perception of virtual clinics in spinal practice and the main challenges involved; 39% of participants reported that the main challenge was the limited ability to perform a physical examination, followed by concerns of medico-legal implications (19%). Surprisingly, only 9% of participants reported problems with technology ( Riew et al, 2021a ).…”
Section: What Do Surgeons Think About Virtual Clinics?mentioning
confidence: 99%